Білім мен ғылымды жан əлемімен дарытқан тұлға, аяулы ғалым-ұстаз, профессор Г.Ш. Жамбатырованың рухына арналады - Исова, Л. Т. (International relations and international law Journal, 2016)
Посвящается человеку, всей душой посвятившему себя знаниям и науке, незаменимому наставнику и ученому, профессору Г.Ш. Жамбатыровой It is devoted to the person who with all the heart has devoted himself to knowledge and science, the irreplaceable mentor and the scientist, professor G. Sh. Zhambatyrova